The Effectiveness Of Sports Massage in Reducing Pain Levels and Increasing The Range Of Motion (ROM) Of Futsal Players' Ankle Joints - Arif Mustopo; Mohamd Mbaydeen; Thesa Rowan (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to test the effectiveness of sports massage on reducing pain and increasing Range of Motion (ROM) of the lower extremities, especially the ankle joint, and to determine its level of effectiveness in futsal players. Methodology: The study used a pre-experimental design with a one group pretest-posttest design. The instruments used were the Visual Analogue Scale (VAS) to measure pain and a goniometer to measure ROM. The sampling technique was carried out incidentally with 20 respondents. Data were analyzed using the Wilcoxon signed ranks test. Main Findings: The results showed that sports massage significantly reduced pain levels and increased ROM in both plantar flexion and dorsiflexion movements. The effectiveness of reducing pain was 50.79%, increasing plantar flexion ROM by 92.19%, and dorsiflexion by 94.49%. Novelty/Originality of this study: This study contributes to the non-pharmacological approach in the management of minor sports injuries, especially muscle pain and mobility limitations. This study shows the effectiveness of sports massage as a cheap, practical, and easy-to-apply physical recovery method for futsal athletes.